Differences between the productivities of organic and conventional dairy farms in Denmark. Issue 1 (10th February 2021) - Aigner, Lorenz; Asmild, Mette
Abstract: The study compares the productivity change over time of organic and conventional dairy farms in Denmark between 2011 and 2018 using data envelopment analysis, and aims to identify which technology is superior. Productivity changes and the differences between organic and conventional frontiers in each year for observations from each group are calculated for each technology separately using the Malmquist Productivity Index and its components. Then, a recently developed permutation test is used to analyse the statistical significance of the results. The analysis identifies volatility in the (economic) production possibilities, which is likely related to changes in milk prices caused by geopolitical events, which the conventional technology seems to be more susceptible to. Furthermore, the organic technology on average became superior for conventional farms in 2015. Farm level analysis identifies characteristics of the input–output mix of the farms, indicating whether a farm could benefit from conversion to the other technology.